A dual solvent evaporation route for preserving carbon nanoparticle fluorescence in silica gel and producing white light-emitting diodes. (16th August 2016) - Cui, Yan; Bu, Xinyuan; Zou, Haoyang; Xu, Xiaowei; Zhou, Ding; Liu, Huiwen; Zhang, Xun; Liu, Yi; Sun, Hongchen; Jiang, Jinlan; Zhang, Hao
Abstract : Luminescent carbon nanoparticles (C-NPs), incorporated with silica gel via a dual solvent evaporation route, are used as the color conversion layer on a InGaN UV-blue emitting chip to produce white-light-emitting diodes. Abstract : Carbon nanoparticles (C-NPs) are novel and competitive luminescent materials both in academic research and practical applications owing to their environment-friendly behavior and high abundance on Earth. Despite the successes in preparing strongly luminescent C-NPs, preserving the luminescence in solid materials is still challenging. With the aim to produce C-NP-based white-light-emitting diodes (WLEDs), in this work, solvent-dispersible C-NPs are embedded into commercial silica gel via a dual solvent evaporation route. The basic idea is to lower the evaporation rate of the solvents, thus leading to a good dispersion of the C-NPs in the silica gel. This method avoids the aggregation-induced emission quenching of C-NPs in solid materials, and therefore preserves the strong luminescence in the C-NPs/silica gel composites. The composites are further blended with polydimethylsiloxane and act as the color conversion layer on InGaN UV-blue emitting chips, which produces LEDs with a bright white emission.